EFFECT OF PH AND ADSORBENT DOSES ON MN (II) METAL ADSORPTION IN THE KALIGARANG RIVER SEMARANG CITY USING SYNTHETIC COCONUT SHELL POWDERED ACTIVATED CARBON (PAC) - Pradnya, Irene Nindita; Triwibowo, Bayu; Wulansarie, Ria; Hanifah, Ririn; Prakasita, Iffat Ganjar Fadhila (CENDEKIA EKSAKTA, 2022)
Kaligarang River is the largest river in the Semarang, which looks clear but actually containing Mn metal above the permitted threshold. Excessive presence of Mn metal can cause problems for human being inside the brain (Parkinson's syndrome), liver, and kidneys. The aim of the study was to analyze the effect of the adsorbent dose and the pH of the solution containing Mn metal. The river water sample was tested at Tirta Moedal PDAM, Semarang; contaminated 1.075 mg/L heavy metal Mn. Based on Government Regulation No. 82 of 2001, the maximum allowable concentration of Mn in water is 0.1 mg/L. Adsorption with activated carbon is an effective method in processing Mn metal pollution. Activated carbon formed as powder from coconut shell size of 500 microns. The adsorption process was with a contact time of 90 minutes and a stirring speed of 210 rpm. The pH variables were pH 3, 7, and 12 and the adsorbent dose was 1, 5, 10 and 15 g /L. The adsorption results showed that the optimum conditions of the adsorption process occurred at pH 3 with an adsorbent dose of 15 g / L with percent absorption of Mn metal of 87.18%. Keywords: Activated carbon, Adsorption, Manganese